The Impact of Traditional and Robotic Toys on 3-4 Years Old's Play - Ryabkova I.A; Pavlovskaia D.V; Sheina E.G (Moscow State University of Psychology and Education, 2022)
Young children's play needs toys, which are its object support and the main tools. Character toys are of particular importance the function of which is the substitution of a character, the embodiment of a role. New technical capabilities make it possible to create complex robotic toys capable of learning, autonomous movement, and reactions to interaction with them. However, the play potential of these toys has not been sufficiently studied. The purpose of this research is to study whether young children (3-4 years old) will play with a robot toy and whether this play will differ from playing with ordinary character toys. The work of P. Kahn et al. was used as the methodological basis of this research. The study included observing a play with two types of toys - a robotic and a stuffed dinosaur, a structured interview, and a classification of cards. The sample consisted of 30 children attending a state kindergarten. The results showed that children are significantly less likely and more monotonous to play with a robotic toy than with a traditional one. At the same time, they interact more with a robotic toy, study it more and are afraid of it as a living being. The results obtained allow us to raise the question of the category of this type of toy: they belong to robots but not to character toys.